Effectiveness of Clinical Decision Tools in Predicting Pulmonary Embolism. (22nd February 2021) - Simon, Michael A.; Tan, Christopher; Hilden, Patrick; Gesner, Lyle; Julius, Barry
Abstract : Objective . The Wells criteria and revised Geneva score are two commonly used clinical decision tools (CDTs) developed to assist physicians in determining when computed tomographic angiograms (CTAs) should be performed to evaluate the high index of suspicion for pulmonary embolism (PE). Studies have shown varied accuracy in these CDTs in identifying PE, and we sought to determine their accuracy within our patient population. Methods . Patients admitted to the Emergency Department (ED) who received a CTA for suspected PE from 2019 Jun 1 to 2019 Aug 31 were identified. Two CDTSs, the Wells criteria and revised Geneva score, were calculated based on data available prior to CTA and using the common D-Dimer cutoff of >500 μ g/L. We determined the association between confirmed PE and CDT values and determined the association between the D-Dimer result and PE. Results . 392 CTAs were identified with 48 (12.1%) positive PE cases. The Wells criteria and revised Geneva score were significantly associated with PE but failed to identify 12.5% and 70.4% of positive PE cases, respectively. Within our cohort, a D-Dimer cutoff of >300 μ g/L was significantly associated with PE and captured 95.2% of PE cases. Conclusions . Both CDTs were significantly associated with PE but failed to identify PE in a significant number of cases, particularly the revised Geneva score. Alternative D-Dimer cutoffs may provide better accuracy in identifying PE cases.